Health-related quality of life and associated factors among COVID-19 individuals managed with Indian traditional medicine: A cross-sectional study from South India - Rajalakshmi Elumalai; Bhavani Shankara Bagepally; Manickam Ponnaiah; Tarun Bhatnagar; Suganya Barani; Poornima Kannan; Lakshmi Kantham; P. Sathiyarajeswaran; Sasikumar D (Elsevier, 2023)
Introduction: Coronavirus disease-2019 (COVID-19) had a multidimensional impact on human life. It affects the health-related quality of life (HRQoL) which is a perceived measure of physical and mental health. We estimated the EuroQol utility value for COVID-19 and the associated factors for those managed at Siddha COVID care centres in Tamil Nadu. Methods: A cross-sectional study was conducted by a telephonic interview of 2000 randomly selected COVID-19 adults tested positive during June 2020 to Jan 2021. We collected sociodemographic, clinical and EQ-5D-5L profile. Mean EQ-5D-5L summary utility values and EQ-VAS scores were estimated. Multivariate regression was used to examine the factors associated with EQ-5D-5L. Study protocol was approved by the Institutional ethics committee of Government Siddha Medical College, Chennai (GSMC-CH-3401/ME-2/050/2021). The committee waived the written informed consent considering the pandemic situation of emerging infectious diseases. Results: We interviewed 1047 participants. Of the total 68% were males with the median age (IQR) of 38 (29-51) years. The mean EQ-5D-5L utility score and EQ-VAS scores are 0.98 ± 0.05 and 92.14 ± 0.39 respectively. COVID-19 asymptomatic group reported a mean utility score of 0.99 ± 0.03 which is relatively more than the symptomatic group (0.97 ± 0.06),. EQ-VAS score was also reported high among the asymptomatic (95.45 ± 5.95) than the symptomatic (91.40 ± 8.69COVID-19. Conclusion: The severity of illness and the comorbidity are significantly associated with a low HRQoL of COVID-19 patients.